2008
DOI: 10.2807/ese.13.13.08079-en
|View full text |Cite
|
Sign up to set email alerts
|

Mumps outbreak ongoing since October 2007 in the Republic of Moldova

Abstract: The Republic of Moldova is experiencing a nationwide mumps outbreak, with a total of 19,550 notified cases as of 23 March 2008. The outbreak started in October 2007, with 105 cases notified in that month compared to an average number of 24 cases per month notified between January and September 2007. Between 1 October and 31 December 2007, 1,524 cases were notified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Cough and dysphagia were seen in 83.3% and 80% of the patients respectively. Our findings were similar to studies done by Arshad et al and Moghe et al 22,23 In a study by Arshad et al, all the patients (100%) were having bilateral parotid enlargement, the hallmark of mumps. 23 Fever was present in 13 (36.1%) boys and 10 (52.6%) girls.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Cough and dysphagia were seen in 83.3% and 80% of the patients respectively. Our findings were similar to studies done by Arshad et al and Moghe et al 22,23 In a study by Arshad et al, all the patients (100%) were having bilateral parotid enlargement, the hallmark of mumps. 23 Fever was present in 13 (36.1%) boys and 10 (52.6%) girls.…”
Section: Discussionsupporting
confidence: 93%
“…Moghe et al reported the median age to be 9.4 years (range: 7 months-38 years) and 97 (60%) were males. 22 In our study, there was no case below 1 year but there were 40 cases between 1 and 5 years, 23 in boys and 17 in girls. The largest number was in the year-group of 6 to 10, with 80 cases, 45 in boys and 35 in girls.…”
Section: Discussionmentioning
confidence: 38%